Investasi pasar modal di Indonesia Perkembangan, kecenderungan, kebutuhan, dan prospek - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1994)
ABSTRACT: indonesia stock market has been growing rapidly since 1989. Although the economic growth has contributed to the development of the market, government policies also played a significant role. The market has become an important alternative for firms to raise funds needed for long term investment. Although various types of securities are traded, trading is dominated by common st'ocks. This phenomenon is expected to continue in the near future. Foreign investors play an important role in the market, and that role is expected to increase. It was detected that the market had satisfied the weak-form efficiency, and there was an indication that the market had become more efficient. Finally, the learning process seemed to be found in the market which may contribute to the informational efficiency of the market. In line with Indonesian economic growth, the stock market is expected to play a bigger role in the financial sector. It is not only an alternative for the firms to obtain . funds used for long term investment, but it also provides an alternative for investors to invest their funds in securities of their liking. It is expected that the market will attract more individual and small investors when open end funds are allowed in the market. Finally, the possibility of relaxing constraint imposed on foreign investors, will give a boost to the' market, and the Indonesian market will become closer to the fully integrated world capital market. This will lower the cost of equity of firms listed in the market. Keywords: invesment, foreign investors